Motivations of Semantic Change In Contemporary Indonesian Slang - Arief Armedi; Hermayani Friska Uli Purba; Nia Mutia Nasution; Sabrina Amanda; Theofany Erlim Limbong; Meisuri Meisuri (CV Edu Tech Jaya, 2026)
This study investigates semantic shifts in twenty Indonesian slang expressions used by Generation Z on X. Using Andreas Blank’s motivational theory, qualitative analysis reveals that cognitive association (28%) and expressivity (24%) are the primary drivers of meaning change. The findings demonstrate that slang development is a systematic response to communicative needs, providing a foundation for understanding linguistic evolution and social behavior in digital environments.